2017
DOI: 10.3390/ijerph14121499
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Counselling Practices among General Practitioners in Croatia

Abstract: Chronic non-communicable diseases are a significant public health problem and imbalanced nutrition is one of the most significant risk factor for them. The objective of this study was to examine Croatia’s general practitioners’ nutrition counselling practice and determine the factors that influence such practice. A cross-sectional study was conducted among 444 (17.0%) randomly selected general practitioners (GPs) in Croatia from May to July 2013 via a 32-item anonymous questionnaire. Study showed that 77.0% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…This study found that only 29% of physicians reported counselling their patients about nutrition often/most of the time, similar to the low proportion (22%) reported by Khandelwal et al 27 and (19%) reported by Dumic et al 10. Besides, 59% of present cohort spent less than 3 min on providing nutrition care during a routine visit.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study found that only 29% of physicians reported counselling their patients about nutrition often/most of the time, similar to the low proportion (22%) reported by Khandelwal et al 27 and (19%) reported by Dumic et al 10. Besides, 59% of present cohort spent less than 3 min on providing nutrition care during a routine visit.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, patients perceive nutrition information from primary care physicians as credible and reliable,6 even more than nutrition advice from dietitians 7. Most primary care physicians acknowledge they have an important role in providing nutrition care to patients and perceive nutrition care as an important aspect of their practice,8 9 especially when patients are at risk based on their dietary habits and body mass index 10. Therefore, the primary care workforce of KSA has a clear opportunity to support the Saudi population to have healthy dietary behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Australia, Saudi Arabia, and the USA have also pointed to the noticeable gap that exists between physicians’ attitudes and their current practice with regard to nutrition and nutrition care, but in these studies, patients did not receive nutrition care despite the largely positive attitudes of their GPs [ 8 , 27 , 28 ]. Considering that, the situation in Croatia can be viewed as not so critical, because the most important thing is that patients eventually get nutrition care, although room for improvement certainly exists, especially in the reorientation of such care toward primary prevention, as already mentioned [ 13 ]. Contrary to the aforementioned studies, studies in Taiwan and Canada have shown that physicians attitudes were strongly associated with providing nutrition care [ 9 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health workers in primary health care settings are particularly important providers of nutrition care, because they can motivate even healthy individuals to adopt healthier lifestyles [ 5 ]. Furthermore, the primary health care setting has been identified as an ideal setting for implementing chronic disease management programs, including the provision of nutrition care [ 1 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation